Tick-borne encephalitis virus-specific RT-PCR--a rapid test for detection of the pathogen without viral RNA purification - Rudenko, N; Golovchenko, M; Cihlárova, V; Grubhoffer, L (Acta virologica, 2004)
Among diseases transmitted by ticks in the Czech Republic, tick-borne encephalitis (TBE) caused by Tick-borne encephalitis virus (TBEV) and Lyme disease caused by Borrelia burgdorferi spirochete are most important. We propose an effective and specific test for detection of TBEV in a single tick or a pool of ticks based on the detection of TBEV RNA using an RT-PCR technique without RNA purification. The method is very sensitive with the detection limit of about 14 fg TBEV RNA in total RNA obtained from brain suspension from suckling mice infected with TBEV per reaction. The primers were derived from the 5'-terminal non-coding region, a highly conserved part of the virus. The method was successfully applied to field-collected ticks in detecting TBEV RNA. This method can be used in studies of several aspects of TBEV: epidemiology, screening of natural foci, circulation and detection of virus genome sequences in clinical materials.
Keywords: RNA, Viral; druhová specificita; RNA virová; klíště; Brain; Nymph; stadia vývoje; Encephalitis Viruses, Tick-Borne; DNA Primers; polymerázová řetězová reakce s reverzní transkripcí; Species Specificity; 5' Untranslated Regions; 5' nepřekládaná oblast; Animals, Suckling; nymfa; Animals; ženské pohlaví; zvířata; Life Cycle Stages; mozek; kojená zvířata; DNA primery; myši; Ixodes; Reverse Transcriptase Polymerase Chain Reaction; viry klíšťové encefalitidy; Mice; Female